The Role of Financial Performance in Going Concern Audit Opinions - Riyanti; Antong; Rahmawati; Halim Usman; Sri Wahyuny Mustafa (IECON: International Economics and Business Conference, 2024)
This study investigates the impact of company size, profitability, liquidity, and company growth on the issuance of going concern audit opinions for manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2019-2023. The research utilizes a sample of 33 manufacturing companies observed over a five-year period, resulting in a total of 165 data points. Logistic regression analysis with panel data is employed to assess the relationship between these variables and going concern audit opinions. The findings indicate that company size and company growth have a negative but statistically insignificant influence on going concern audit opinions. This suggests that these factors do not substantially contribute to the likelihood of receiving a going concern opinion. Conversely, profitability and liquidity exhibit a positive and significant impact on going concern audit opinions. This highlights that higher profitability and liquidity enhance a company's ability to continue its operations, reducing the auditors' concerns about its viability. These results provide valuable insights for stakeholders, including auditors and management, emphasizing the importance of financial performance metrics in determining going concern status. Future studies could explore other factors, such as corporate governance and external economic conditions, to provide a more comprehensive understanding of determinants influencing going concern audit opinions.